Pemberdayaan Perempuan melalui Home Industri menuju Ekonomi Kreatif di Kota Batam - Riska Abdilah Nasution; Ayang Marsnely; Hagi Arfilindo; Friyatmi; Susi Evanita (Manaruko: Jurnal Pengabdian Masyarakat, 2023)
The women's empowerment program through the home industry of water hyacinth is motivated by human resources who have a skill in the field of crafts. The existence of this home industry opens up job opportunities and takes advantage of the potential of the surrounding community. One of them is the water hyacinth plant, if cultivated, will produce creative crafts and have high economic value. The purpose of this study is to describe the strategy of empowering women through the water hyacinth home industry in Masang Isna Puring Village, Batam. Methods This research uses qualitative research, data collection uses interview and observation techniques. The informants of this research are the owner of the Isna Puring home industry and women's craftsmen. The results showed that the women's empowerment strategy went through the stages of planning, implementation, evaluation, as well as supporting and inhibiting factors for empowerment. The conclusions of the research on the strategy of empowering women through the home industry of aceng hyacinth are able to improve the community's economy and reduce community unemployment in Masang Isna Puring village, Batam